Clinical management of patients with ASXL1 mutations and Bohring–Opitz syndrome, emphasizing the need for Wilms tumor surveillance. (29th April 2015) - Russell, Bianca; Johnston, Jennifer J.; Biesecker, Leslie G.; Kramer, Nancy; Pickart, Angela; Rhead, William; Tan, Wen‐Hann; Brownstein, Catherine A.; Kate Clarkson, L.; Dobson, Amy; Rosenberg, Avi Z.; Vergano, Samantha A. Schrier; et al.
<x xml:space="preserve">Abstract</x> Bohring–Opitz syndrome is a rare genetic condition characterized by distinctive facial features, variable microcephaly, hypertrichosis, nevus flammeus, severe myopia, unusual posture (flexion at the elbows with ulnar deviation, and flexion of the wrists and metacarpophalangeal joints), severe intellectual disability, and feeding issues. Nine patients with Bohring–Opitz syndrome have been identified as having a mutation in ASXL1. We report on eight previously unpublished patients with Bohring–Opitz syndrome caused by an apparent or confirmed de novo mutation in ASXL1. Of note, two patients developed bilateral Wilms tumors. Somatic mutations in ASXL1 are associated with myeloid malignancies, and these reports emphasize the need for Wilms tumor screening in patients with ASXL1 mutations. We discuss clinical management with a focus on their feeding issues, cyclic vomiting, respiratory infections, insomnia, and tumor predisposition. Many patients are noted to have distinctive personalities (interactive, happy, and curious) and rapid hair growth; features not previously reported. © 2015 Wiley Periodicals, Inc.